2021
DOI: 10.1101/2021.07.26.453749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information silos distort biomedical research

Abstract: Information silos have been an oft-maligned feature of scientific research for introducing a bias towards knowledge that is produced within a scientist's own community. The vastness of the scientific literature has been commonly blamed for this phenomenon, despite recent improvements in information retrieval and text mining. Its actual negative impact on scientific progress, however, has never been quantified. This analysis attempts to do so by exploring its effects on biomedical discovery, particularly in the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 42 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…There is also a reporting bias, as negative results, and failed replications often remain unknown to those outside that silo. This reality can distort the literature by maintaining prevailing theories that are solely based on “positive” results 4,63 . These challenges may be reduced incrementally in the future as NIH recently published a Data Management and Sharing requirement that promotes sharing and broad accessibility to research data for reuse and external validation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is also a reporting bias, as negative results, and failed replications often remain unknown to those outside that silo. This reality can distort the literature by maintaining prevailing theories that are solely based on “positive” results 4,63 . These challenges may be reduced incrementally in the future as NIH recently published a Data Management and Sharing requirement that promotes sharing and broad accessibility to research data for reuse and external validation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, across the scientific spectrum, research is increasingly specialized, making it difficult to identify innovative connections beyond one's own area of research 3 . Rodriguez‐Esteban showed that bias resulting from biomedical siloization coupled with the extraordinary growth of the scientific literature distorts and hinders scientific progress 4 . For those focusing on back pain research, the resulting information silos can lead to narrow and biased syntheses of research observations and underrepresentation of crosstalk among biological, psychological, and social processes that mediate pain experiences over time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations